2019
DOI: 10.1111/apa.15025
|View full text |Cite
|
Sign up to set email alerts
|

Using a peer mentorship approach improved the use of neonatal continuous positive airway pressure and related outcomes in Malawi

Abstract: Aim This study evaluated whether peer mentorship was an effective and sustainable way of improving and maintaining knowledge and skills on neonatal continuous positive airway pressure (CPAP) in a low‐resource setting with a high turnover of healthcare providers. Methods The Malawi Ministry of Health recruited five nurses with considerable CPAP experience and provided them with mentorship training from July to August 2014. The mentors then provided 1‐week on‐site mentorship for 113 colleagues at 10 secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…30 The WHO recommends following up 4 weeks after the initial IMCI training course to help reinforce the skills learnt, and continued supervision. 31 There are examples of successful mentorship within child health, 32 33 and community case management in Malawi. However, as lacking supervision and mentorship was raised by healthcare workers in the FGDs, work is needed on effective adoption at frontline facilities.…”
Section: Discussionmentioning
confidence: 99%
“…30 The WHO recommends following up 4 weeks after the initial IMCI training course to help reinforce the skills learnt, and continued supervision. 31 There are examples of successful mentorship within child health, 32 33 and community case management in Malawi. However, as lacking supervision and mentorship was raised by healthcare workers in the FGDs, work is needed on effective adoption at frontline facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This requires well-trained emergency care workers. In this issue, Asibon et al 7 The deployment of low-cost CPAP in Malawi followed remarkable results obtained in a quasi-randomised study of CPAP vs standard nasal oxygen conducted in the neonatal unit of the referral hospital of southern Malawi. In that study, CPAP was found to be highly efficacious with survival of 71% vs 44% in controls.…”
Section: Peer Mentorship In the Scale-up Of Neonatal Continuous Positmentioning
confidence: 98%
“…This requires well‐trained emergency care workers. In this issue, Asibon et al 7 describe a peer mentorship approach to in‐service training of health workers as part of the deployment of CPAP in Malawi. They report impressive 3‐month before‐and‐after increases in the competence of mentored nurses and CPAP use.…”
mentioning
confidence: 99%
“…In the 18 studies which measured skills alongside knowledge, capacity strengthening was conceptualised as both increases in content knowledge and observed practice, over a range of topics ranging from health promotion [32] to disease surveillance [33], and infection control [34]. One study related to ability to coach clinical skills and quality improvement [35], and another to the management of substance use conditions [36], with all other studies related to more technical skills, such as breast ultrasound interpretation [37], surveillance [33] and neonatal continuous positive airway pressure [38].…”
Section: Objective 1: Domains Of Capacity Strengtheningmentioning
confidence: 99%
“…The majority of studies (n = 36) measured outcomes in terms of a percentage change in the domain between pre-and post-intervention-whether objective or subjective-and the statistical significance of this change. Fourteen studies combined this with observation and six relied on observation alone to observe changes in knowledge, skills or practice [31,38,[68][69][70][71]. In some cases, strengthened capacity through observation was rated as a percentage improvement [31], and in other cases, it was simply observed [57].…”
Section: Objective 2: Measurements Of Capacity Strengtheningmentioning
confidence: 99%